Revisión especial de la cuenta inventario y su incidencia en la rentabilidad de la empresa Kamied S.A, cantón Quevedo, año 2012 - Collantes Villalta, Tania Elizabeth (2015)
This research was conducted in KAMIED S.A, the canton Quevedo, had as main objective to carry out a review of the inventory account and its impact on the profitability of the company. The results demonstrate the shortcomings of the system of internal control leading company KAMIED S.A, in the area of inventories may determine that do not have an internal control system influencing the process inventories with obvious consequences to processes, was identified as are considered unsuitable. The current situation of the company in general in the administration of inventories management deficiencies exist, so determined not to have procedures manuals for that area, causing some processes within the inventory is not properly conducted. Inventories are valued at actual cost of the investment and have an acid test ratio showing the ability of the company to meet its short-term obligations with its most liquid assets. In the case of the company this index is 0.23 and likewise shows the efficiency of liquidity to cover current liabilities without inventories. The report of the results allowed us to establish the following findings: lack of manuals to guide an internal control in the company, lack of practice of physical inventories for comparison with the system, lack of preparation of reports slow-moving inventories and / or fallen in obsolescence and lack of internal control weaknesses originates in the settings of the fiscal year.